Cultural values and changes in happiness in 78 countries during the COVID-19 pandemic: An analysis of data from the World Happiness Reports - Rajkumar, Ravi Philip (Frontiers in Psychology, 2023)
The concept of happiness is consistent to a significant extent across cultures, and encompasses both internal (subjective) and external (situational) aspects. Cultural values and norms shape emotions and behavior from an early age, and hence play a key role in influencing cross-national variations in happiness. Cross-national variations in culture can thus play a key role in influencing the relationship between adverse circumstances, such as the COVID-19 pandemic, and happiness. The current study examines the relationship between the six dimensions of culture, defined by Hofstede and his colleagues, and subjective ratings of happiness in 78 countries, obtained before (2017-19) and during (2020-21) the COVID-19 pandemic, based on data from the most recent World Happiness reports. The key results were: (a) countries were as likely to experience an increase as a decrease in self-reported happiness during this period; (b) distinct domains of culture were significantly correlated with happiness at each time point, though there was a certain degree of overlap; (c) pre-pandemic levels of happiness were negatively associated with changes in happiness during the pandemic; and (d) among cultural dimensions, long-term orientation was positively associated with changes in subjective happiness, while indulgence was negatively associated with this variable. Certain cultural values may play an important part in fostering a path to well-being in the face of stressful or traumatic circumstances. This path may be similar to the concept of mature happiness, derived from existential philosophy, which is characterized by achieving a balance between the positive and negative aspects of one’s life.